2020
DOI: 10.1139/cjfas-2019-0034
|View full text |Cite
|
Sign up to set email alerts
|

Kokanee–sockeye salmon hybridization leads to intermediate morphology and resident life history: implications for fisheries management

Abstract: Stocking programs designed to return extirpated species to their historical range have become increasingly prevalent, punctuating the need to better understand the risks posed to recipient ecosystems. Here, we investigated the genetic and biological consequences of an anadromous sockeye salmon (Oncorhynchus nerka) stocking program in Skaha Lake, British Columbia, where substantial levels of hybridization and introgression with the native freshwater resident ecotype (kokanee) have been detected. We genetically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 53 publications
3
14
0
Order By: Relevance
“…This program provides an excellent opportunity to investigate the extent and outcomes of intra-specific hybridization between O. nerka migratory and resident forms outside of a laboratory setting. Previous research examining hybridization between sockeye salmon and kokanee found O. nerka hybrids occupy intermediate morphologies and exhibit a largely resident life history, although this latter finding requires further investigation 12 , 29 . These studies employed genetic marker sets that were effective at differentiating pure-stock from hybrid, however, they had limited power for the identification of advanced hybrid classes that has become increasingly important for genetic monitoring as the reintroduction program matures.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…This program provides an excellent opportunity to investigate the extent and outcomes of intra-specific hybridization between O. nerka migratory and resident forms outside of a laboratory setting. Previous research examining hybridization between sockeye salmon and kokanee found O. nerka hybrids occupy intermediate morphologies and exhibit a largely resident life history, although this latter finding requires further investigation 12 , 29 . These studies employed genetic marker sets that were effective at differentiating pure-stock from hybrid, however, they had limited power for the identification of advanced hybrid classes that has become increasingly important for genetic monitoring as the reintroduction program matures.…”
Section: Introductionmentioning
confidence: 88%
“…We genotyped tissue samples from O. nerka spawners in the Okanagan River upstream of Skaha Lake that were previously sampled in 2016 (n = 45) and 2017 (n = 59) 29 , and newly sampled in 2019 (n = 218; this study) as deadpitch (post-mortem carcass collection after spawning) by personnel from the BC Ministry of Forests, Lands, Natural Resource Operations, and Rural Development. The section of river that was sampled represents the only spawning habitat that exists for O. nerka populations from Skaha Lake and all forms spawn within this section of river.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal value of K was then combined across ten independent runs with CLUMPP [ 45 ]. We also assessed individual assignment accuracy with the Rannala and Mountain (1997) estimator as implemented in ONCOR with 100 simulated individuals per population based on empirical genotype frequencies with recom-sim [ 46 48 ]. After assessment, we sent the full RAD tag sequences associated with the pool of candidate SNPs to GTseek LLC ( https://gtseek.com/ ) for custom locus-specific primer design.…”
Section: Methodsmentioning
confidence: 99%